Perbedaan Kadar 25 (OH)D Serum menurut Pola Makan Sirkadian pada Remaja Putri Etnis Minangkabau - Silvia, Elwitri (Indonesian Journal of Nutrition Science and Food; Vol 1 No 2 (2022): Januari 2022, 2022)
Vitamin D deficiency is associated with problem in female reproductive cycle. The main source of vitamin D comes from sunlight but living in tropical country doesn’t shot adequate serum 25(OH)D levels. Vitamin D levels are not only affacted by sun exposure but also  affacted by circadian behaviour. The purpose of this study was to determine differences in serum 25(OH)D levels according to circadian eating patterns in Minangkabau ethnic adolescent girls. The study was conducted with a cross-sectional design on adolescent girls at Andalas University. Circadian diet was calculated from 24-h food recall and Nutrisurvey 2007.  Serum 25 (OH)D level was quntified by ELISA method. More than half of subject (n=48; 60%) were deficient in vitamin D and most of subject had pDT circadian diet (n=68;85%). There was a significant difference in serum 25(OH)D levels between pDT dan pNT circadia diet. Serum 25(OH)D were higher in pDT and pNT data group. Vitamin D deficiency is prevalent in Minangkabau adolescents. The pDT circadian diet can be a solution in improving vitamin D status in Minangkabau adolescents.